2018
DOI: 10.5194/hess-2018-144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water ages in the critical zone of long-term experimental sites in northern latitudes

Abstract: Abstract. As northern environments undergo intense respond due to a warming climate and altered land use practices, there is an urgent need for improved understanding of the impact of atmospheric forcing and vegetation on water storage and flux dynamics in the critical zone. We therefore assess the age dynamics of water stored in the upper 50 15 cm of soil, and in evaporation, transpiration or recharge fluxes at four soil-vegetation units of podzolic soils in the northern latitudes with either heather or tree … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 66 publications
1
43
0
Order By: Relevance
“…As the upper soil layers usually contain relatively young waters (see section ), the soil evaporation flux should also contain young water. Soil physical simulations indicate that the mean ages of evaporative fluxes range between 1 and about 50 days at sites in northern latitudes (Sprenger, Tetzlaff, Buttle, Buttle, Laudon, & Soulsby, ). Generally, the partitioning between evaporation and transpiration flux is challenging, but increasingly applied in situ stable isotope measurements were shown to allow distinguishing between both fluxes (Wang et al, ).…”
Section: How Interfaces Affect Water Age Distributionsmentioning
confidence: 99%
“…As the upper soil layers usually contain relatively young waters (see section ), the soil evaporation flux should also contain young water. Soil physical simulations indicate that the mean ages of evaporative fluxes range between 1 and about 50 days at sites in northern latitudes (Sprenger, Tetzlaff, Buttle, Buttle, Laudon, & Soulsby, ). Generally, the partitioning between evaporation and transpiration flux is challenging, but increasingly applied in situ stable isotope measurements were shown to allow distinguishing between both fluxes (Wang et al, ).…”
Section: How Interfaces Affect Water Age Distributionsmentioning
confidence: 99%
“…As a consequence, soil water is a mixture of previous events with different isotope compositions and different ages. Analytical tools to infer ages of water leaving soils (e.g., Kim et al, ; Sprenger, Tetzlaff, Buttle, Laudon, & Soulsby, ; Benettin, Queloz, Bensimon, McDonnell, & Rinaldo, ) parallel to those used in catchments (e.g., Harman, ) reflect how rainfall mixes with stored waters. Of course, age contrasts only manifest in isotopic differences if precipitation isotope ratios vary over time so age can be inferred.…”
Section: Contrasts In Tracers Are Consistent With Water Age Contrastsmentioning
confidence: 99%
“…Therefore, we need to move beyond reporting isotopic differences between stores, and instead, we should use these isotopic contrasts between plants and streams to infer the ages of waters stored in soils and of those flowing through them. Such analysis can be completed using detailed models with intensive data requirements (e.g., Harman, ; Benettin et al, ; Knighton et al, ; Evaristo et al, ; Sprenger, Tetzlaff, Buttle, Laudon, Soulsby, et al, ) or using simple point measurements and back of the envelope calculations (e.g., Ehleringer et al, ; Allen, Kirchner, et al, ). Examining these age contrasts ultimately supports better system understanding and more accurate predictions.…”
Section: Is New Theory Needed?mentioning
confidence: 99%
“…In terms of vegetation impacts on catchment hydrology, previous studies have shown that a prolonged growing season can enhance plant growth and thus increase transpiration (Berninger, 1997;Hwang et al, 2014). In these low-energy northern catchments, soil evaporation is limited, and transpiration contributes most of the total evapotranspiration (Sprenger et al, 2018;Wang et al, 2018). Increases in transpiration can result in a decline in streamflow (Deutscher et al, 2016;Kim et al, 2018).…”
Section: The Hydrologic Consequences Of Vegetation Phenology Changementioning
confidence: 99%